Microvascular Decompression using muscle graft for interposition: A retrospective study - Karki, Prasanna; Joshi, Sumit; Paudel, Prakash; Shah, Damber Bikram; Sharma, Gopal Raman (Nepal Journal of Neuroscience, 2021)
Objective: This studies aims to evaluate the outcome of Microvascular Decompression (MVD) using a muscle graft for interposition in Trigeminal Neuralgia (TN), Hemifacial Spasm (HFS) and Glossopharyngeal Neuralgia (GPN). All surgeries were performed by a single surgeon (G.R.S). Methods: In total, 26 patients with TN, HFS and GPN underwent MVD from September 2007 to April 2019. All the patients were either medically refractory or poor symptom tolerance. The mean follow-up period was 72 months. Results: Each MVD was performed using an autologous muscle graft with interposition of vessels. One patient (3.84%) had reoccurrence after MVD with muscle graft and two patients (7.69%) had partial relief. Conclusion: Various types of prosthesis are used for transposition and interposition of vessels in MVD surgeries. Although in our case series we didn't use any prosthesis for the comparative outcome, the use of muscle graft showed minimal reoccurrence rate with benefit of being cost effective. Therefore, we need randomized controlled trials to prove the superiority of muscle graft from other prosthesis material.